Polycarbonate resin composition
By introducing isosorbide skeleton and branched polysiloxane into the polycarbonyl acid ester resin, the problem of insufficient impact of the wear of the resin during cleaning and external dust on transparency and aesthetics is solved, and a resin with high transparency and wear resistance is achieved.
Patent Information
- Application Number
- JP2019112749
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-06-19
- Filing Date
- 2019-06-18
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2039-06-18
AI Technical Summary
The wear of existing polycarbonyl acid ester resins during cleaning and the impact of external environment dust on transparency and aesthetics is insufficient, especially in terms of wear resistance during cleaning and protection of external dust.
Polycarbonate resin containing isosorbide skeleton and branched polysiloxane are used as components, and the wear resistance and transparency of the resin are improved through reasonable component ratios and functional group content.
It achieves the improvement of the wear resistance of the resin and the protection of external dust while maintaining high transparency, extends the service life of the resin and improves its aesthetics.
Smart Images

Figure 0007667634000001 
Figure 0007667634000002 
Figure 0007667634000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polycarbonate containing a polycarbonate resin and a branched polyorganosiloxane. The present invention relates to a carbonate resin composition and a molded article made from the same. [Background technology]
[0002] In recent years, due to environmental considerations, ether-containing esters, such as isosorbide, which is a plant-derived raw material, have become more widely used. Polycarbonate resins using diols have been developed (see Patent Documents 1 and 2). Polycarbonate resin using isosorbide has excellent heat resistance, weather resistance and impact resistance. It is also known that the coating is applied to automobile interior and exterior parts (see Patent Document 3).
[0003] On the other hand, a polycarbonate resin containing a structural unit derived from isosorbide and a silicone Resin compositions containing a compound are also known (see Patent Document 4). It is described that the inclusion of the corn compound improves scratch resistance. In Patent Document 5, a polycarbonate resin containing a structural unit derived from isosorbide and a di Silicone compounds with organosiloxane structure or specific organosilosequioxane structure By containing this compound, scratch resistance is improved and the transparency of the molded product is good. It is described that the composition is excellent in initial appearance, mechanical properties, etc. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. WO2004 / 111106 [Patent Document 2] International Publication No. WO2007 / 063823 [Patent Document 3] JP 2013-209585 A [Patent Document 4] JP 2015-199954 A [Patent Document 5] JP 2017-008140 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, molded products using polycarbonate resins having structural units derived from isosorbide have been It is being considered for use in interior and exterior parts for automobiles and other vehicles. In order to prevent scratches that occur when wiping with a cloth, it is important to improve the slipperiness and abrasion resistance. Furthermore, it is required to improve the transparency and the beauty of the molded product while being resistant to outdoor environmental dust. Therefore, it has become desirable to further improve the abrasion resistance when wiping off muddy water.
[0006] However, the compositions of conventional polycarbonate resin compositions such as those in Patent Documents 4 and 5 are The molded product is resistant to wiping off muddy water containing dust from outdoor environments while maintaining high transparency. There is still room for improvement in terms of increasing the abrasion resistance of the film. Furthermore, the transparency is also insufficient. do.
[0007] The object of the present invention is to solve the above problems of the conventional products and to provide a molded product having a high transparency while maintaining the high transparency. Also, a high-quality molded product with improved abrasion resistance when wiping off muddy water containing outdoor environmental dust can be obtained. The present invention aims to provide a polycarbonate resin composition capable of producing a molded article comprising the same. . [Means for solving the problem]
[0008] As a result of intensive research to solve the above problems, the present inventors have found that a specific polycarbonate A polycarbonate resin containing a resin (A) and a specific branched polyorganosiloxane (B). The oil composition can wipe off muddy water containing dust from outdoor environments while maintaining the transparency of the molded product. The present inventors have found that it is possible to realize a high-quality molded product having improved wear resistance when the molded product is subjected to the above-mentioned treatment, thereby completing the present invention. That is, the present invention has the following features.
[0009] [1] A resin composition comprising the following (A) and (B): A polycarbonate resin (A) having an isosorbide skeleton, Branched polyorganosiloxane (B). [2] The branched polyorganosiloxane (B) is the entire cascade that constitutes the polyorganosiloxane. M units for isotopic elements (R 1 R 2 R 3 SiO 1 / 2 ) content is 10 mol% or more, and T units (R 6 SiO 3 / 2 ) content is 80 mol % or less The resin composition according to [1], [3] The branched polyorganosiloxane (B) has a reactive functional group and / or a compatible group. The resin composition according to [1] or [2]. [4] The branched polyorganosiloxane (B) is an organosiloxane having an alkenyl group, an ester group, a methacryloyl group, At least one of the following groups: yl group, acryloyl group, cyclic ether group, and alcoholic hydroxyl group [1] to [3], which has a group as a reactive functional group and / or a compatible group. Resin composition. [5] Branched polyorganosiloxane (B) is heated at 110°C under a reduced pressure of 0.15 torr. The weight loss when heated at room temperature for 2 hours is 10% by weight or less. The resin composition described above. [6] The amount of reactive functional groups per 1,000 molecular weight of the branched polyorganosiloxane (B) and the total content of the compatible groups is 1 to 12. composition. [7] The branched polyorganosiloxane (B) is liquid at atmospheric pressure and 20°C, [1] to [6] The resin composition according to any one of the above. [8] The reactive functional group of the branched polyorganosiloxane (B) is an alcoholic hydroxyl group. The resin composition according to any one of [1] to [7], [9] The alcoholic hydroxyl group according to [8], wherein the alcoholic hydroxyl group has a structure represented by formula (12): Resin composition. [ka] (R in Equation (12) 11 is a divalent organic group.
[10] Trimethylsiloxy groups for all M units of branched polyorganosiloxane (B) The resin composition according to any one of [1] to [9], wherein the amount of the at least one substituent is 50 mol % or less.
[11] The branched polyorganosiloxane (B) contains a trimethylsiloxy group in its structure. The resin composition according to any one of [1] to
[10] , which is a branched polyorganosiloxane. thing.
[12] A molded article comprising the resin composition according to any one of [1] to
[11] .
[13] A method for producing a resin composition, comprising mixing the following (A) and (B): A polycarbonate resin (A) having an isosorbide skeleton, Branched polyorganosiloxane (B).
[14] A method for producing a molded article, comprising molding the resin composition according to
[13] . Effect of the Invention
[0010] The polycarbonate resin composition can provide a molded product having high transparency and high abrasion resistance. This makes it possible to prevent scratches and abrasion that occur during use of molded products. In other words, molded products can withstand not only scratches caused by wiping with a rag or tissue, This results in less wear and tear caused by dust contained in environmental dust, and excellent wear resistance. For example, in applications where visibility is required, the decrease in visibility can be suppressed. This allows the molded product to maintain its transparency while maintaining high abrasion resistance. Quality molded products can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The embodiments of the present invention will be described in detail below. The following is an example of an embodiment of the invention, and the present invention is not limited to the following contents as long as it does not exceed the gist of the invention. do not have. In addition, when the expression "~" is used in this specification, the numerical values before and after it In addition, the numerical values described as upper and lower limits are used to mean physical values. The terms "physical value" and "physical value" are used in the sense of including the value.
[0012] [Polycarbonate resin (A)] The polycarbonate resin composition contains a polycarbonate resin (A). The carbonate resin (A) is derived from a dihydroxy compound represented by at least the following formula (1): The polycarbonate includes a structural unit (hereinafter, appropriately referred to as "structural unit (a1)"). The copolymer resin (A) may be a homopolymer of the structural unit (a1), or a copolymer of the structural unit (a1) From the viewpoint of increasing the molecular weight, impact resistance, From the viewpoint of further improving the impact resistance, the polycarbonate resin (A) is a copolymer. It is preferable.
[0013] [ka]
[0014] The dihydroxy compound represented by formula (1) is a stereoisomeric compound, These include isomannide (i.e., ISB), isomannide, and isoidet, each of which may be used alone. They may be used alone or in combination of two or more. Among these, ISB is the most popular due to its ease of availability and manufacturing, weather resistance, optical properties, moldability, and heat resistance. ISB is an abundant plant-derived resource and is the most preferred from the standpoint of carbon neutrality. Sorbitol is produced from a variety of starches that are readily available and are present in the The result is obtained by combining
[0015] Incidentally, the dihydroxy compound represented by formula (1) is easily gradually oxidized by oxygen. Therefore, when handling during storage or manufacturing, care must be taken to prevent moisture from entering the product in order to prevent decomposition by oxygen. It is also preferable to use an oxygen scavenger or to keep the temperature in a nitrogen atmosphere. For example, when isosorbide is oxidized, decomposition products such as formic acid may be generated. When isosorbide containing the solution is used as a raw material for the production of polycarbonate resin, the obtained There is a risk of discoloration of the polycarbonate resin and the polycarbonate resin composition. Not only may it significantly deteriorate the properties of the material, but it may also affect the polymerization reaction and produce high molecular weight polymers. may not be obtained.
[0016] The polycarbonate resin (A) contains an aliphatic dihydroxy compound as the structural unit (a2). , alicyclic dihydroxy compounds, and ethers other than the dihydroxy compounds represented by formula (1) and one or more dihydroxy compounds selected from the group consisting of dihydroxy compounds containing an aryl group (hereinafter Hereinafter, these may be referred to as "other dihydroxy compounds". 2-1). That is, it is preferable that the polycarbonate resin (A) is a copolymer containing the polycarbonate resin (A). is preferably a copolymer containing the structural unit (a1) and the structural unit (a2-1). In this case, the impact resistance of the polycarbonate resin (A) can be improved.
[0017] The aliphatic dihydroxy compound may be a straight-chain aliphatic dihydroxy compound or a branched It may be a dihydroxy chain aliphatic compound, for example, ethylene glycol, 1,3-propanediol, propanediol, 1,2-propanediol, 1,4-butanediol, 1,3-butane Diol, 1,2-butanediol, 1,5-pentanediol, 1,6-hexanediol 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol , 1,10-Decanediol, 1,11-Undecanediol, 1,12-Dodecanediol Examples include
[0018] Examples of the alicyclic dihydroxy compound include 2,2,4,4-tetramethyl-1,3 -Cyclobutanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexa Dimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol , Pentacyclopentadecanedimethanol, 2,6-Decalinedimethanol, 1,5-Decacyclopentadecanedimethanol Calindimethanol, 2,3-Decalindimethanol, 2,3-Norbornanedimethanol Examples of the dimethanol include 2,5-norbornane dimethanol and 1,3-adamantanedimethanol. do.
[0019] Examples of the ether group-containing dihydroxy compound include diethylene glycol, triethylene glycol, and the like. Ethylene glycol, polyethylene glycol (molecular weight 150-2000), poly-1,3 -Propylene glycol, polytetramethylene glycol.
[0020] From the viewpoint of increasing the heat resistance of the polycarbonate resin (A), other dihydroxy compounds The compound is preferably an aliphatic dihydroxy compound or an alicyclic dihydroxy compound, and more preferably an alicyclic dihydroxy compound. Dihydroxy compounds are more preferred. From the viewpoint of further improving heat resistance and impact resistance, Among the alicyclic dihydroxy compounds, cyclobutanediol, cyclohexanedimethanol, Preferred are tricyclodecane dimethanol.
[0021] In the polycarbonate resin (A), the structural unit (a2) such as the structural unit (a2-1) The content is 10 mol% relative to 100 mol% of all structural units derived from dihydroxy compounds. It is preferably 20 mol % or more, more preferably 20 mol % or more, and even more preferably 30 mol % or more. It is preferably 60 mol % or less, more preferably 50 mol % or less, and even more preferably 45 mol % or less. By adjusting the content of the structural unit (a2) within this range, it is possible to obtain a polycarbonate resin. It is possible to improve both the impact resistance and heat resistance of the fat in a well-balanced manner.
[0022] Polycarbonate resin (A) is a commonly used method for producing polycarbonate resins. The polycarbonate resin (A) can be produced, for example, by dissolving in a solution using phosgene. polymerization method, or melt polymerization method in which a carbonate diester is reacted with a dihydroxy compound. It can also be manufactured.
[0023] When manufacturing polycarbonate resin (A), a filter is used to prevent contamination by foreign matter. It is preferable to install a filter downstream of the extruder. The size (opening) of the filter for removing foreign matter is usually 100μm or less, which is the filtration accuracy for removing 99% of the foreign matter. In particular, when it is necessary to avoid the inclusion of minute foreign matter in film applications, 40 μm or less is preferable. It is more preferable, and even more preferable that it is 10 μm or less.
[0024] From the viewpoint of preventing the inclusion of foreign matter after extrusion, the extrusion of the polycarbonate resin (A) is performed as follows: A clean room with a higher level of cleanliness than Class 7 defined in JIS B9920 (2002) It is preferable to carry out the test in a clean room with a cleanliness level of Class 6 or higher. It is advisable to carry out the test in a team.
[0025] In addition, when the extruded polycarbonate resin (A) is cooled and made into chips, it can be cooled by air or water. It is preferable to use a cooling method such as the above. The air used for air cooling should be filtered through a HEPA filter or similar. It is preferable to remove foreign matter from the container before use to prevent foreign matter in the air from reattaching to the container. The water used for cooling is treated with ion exchange resin to remove metals, and then filtered to remove foreign matter. It is preferable to use a filter that has had the particles removed. The opening of the filter is 99% removal. The precision is preferably 0.45 to 10 μm.
[0026] The molecular weight of the polycarbonate resin (A) can be expressed by reduced viscosity. The reduced viscosity is preferably 0.30 dL / g or more, and 0.3 The reduced viscosity is preferably 1.20 dL / g or less, more preferably 5 dL / g or more. The reduced viscosity is more preferably 1.00 dL / g or less, and even more preferably 0.80 dL / g or less. By adjusting the amount of the resin to fall within the above range, the flowability during molding can be improved, and the productivity and Therefore, moldability can be improved. Therefore, molded products of complex shapes can be manufactured with high productivity. This makes it suitable for use in electrical and electronic equipment parts, automotive interior and exterior parts, etc. The reduced viscosity of polycarbonate resin (A) was measured using methylene chloride as a solvent. The concentration of was precisely adjusted to 0.6 g / dL and the temperature was 20.0°C ± 0.1°C. Measure using a viscosity tube.
[0027] The glass transition temperature of the polycarbonate resin (A) is preferably 90° C. or higher. From the same viewpoint, the heat resistance of the polycarbonate resin composition is further improved. The glass transition temperature of the carbonate resin (A) is preferably 100° C. or higher, more preferably 110° C. or higher. On the other hand, the glass transition temperature of the polycarbonate resin (A) is preferably 145° C. or lower. In this case, the flowability during molding is increased, and even molded products with complicated shapes can be molded. This makes it easier for the resin composition to reach the ends of the molding die, thereby making it possible to obtain the desired molded product. In addition, the decrease in strength at the welds can be suppressed. Therefore, the glass transition temperature of the polycarbonate resin (A) is more preferably 135° C. or lower, and A temperature of 25°C or less is even more preferable.
[0028] The polycarbonate resin composition contains one type of resin as the polycarbonate resin (A). The type of structural unit (a2) derived from another dihydroxy compound may be contained alone. Two or more resins having different copolymerization ratios, physical properties, etc. may be mixed together.
[0029] [Branched polyorganosiloxane (B)] The polyorganosiloxane is a polymer having a siloxane bond as a main chain. It refers to a compound having a branched structure in the xane skeleton, for example, represented by the general composition formula (2) shown below. can be. (R 1 R 2 R 3 SiO 1 / 2 ) a (R 4 R 5 SiO 2 / 2 ) b (R 6 SiO 3 / 2 ) c ( SiO 4 / 2 ) d (O 1 / 2 R 7 ) e (O 1 / 2 H) f (2) In formula (2), R 1 From R 6 are independently a hydrocarbon group having 1 to 20 carbon atoms, a reactive functional group, is selected from a solubilizing group and a hydrogen atom, and satisfies a+b+c+d=1. 7 is selected from organic groups having 1 to 7 carbon atoms. In general, (R 1 R 2 R 3 SiO 1 / 2 The siloxy unit represented by R 4 R 5 SiO 2 / 2 The siloxy unit represented by R 6 SiO 3 / 2) represented by Shiro The oxy unit is the T unit, (SiO 4 / 2 ) is called a Q unit.
[0030] The branched polyorganosiloxane (B) is a polyorganosiloxane having a branched structure. Examples of the compound include, but are not limited to, a compound having a reactive functional group, a compatible group, or both a reactive functional group and a compatible group. Here, the reactive functional group is preferably a carbon atom, a hydrogen atom, an oxygen atom, a nitrogen atom, or the like. One or more atoms selected from the group consisting of nitrogen atoms, sulfur atoms, phosphorus atoms, silicon atoms, and halogens. It is composed of atoms and does not exhibit different functional groups within the temperature range of normal use or processing in air or solvent. A group whose chemical structure can change when it comes into contact with a functional group or when it is heated. The solubilizing group is an ionic group that is capable of interacting with the entire or a part of the constituent elements of the polycarbonate resin (A). Polycarbonate resin (A) is separated from the polymer by interactions such as molecular interactions, hydrogen bonds, and dipole-dipole interactions. The reactive functional group is a group that improves the compatibility of the branched polyorganosiloxane (B). In addition to the defined reactivity, compatibility may also be present. The compound may have a compatible group at the same time, and may have a plurality of reactive functional groups and / or a plurality of compatible groups. It may have.
[0031] The total content of the reactive functional group and the compatible group is not particularly limited, but preferably, More preferably, the branched polysiloxane (B) has at least one branched polysiloxane per 1,000 molecular weight. The number is 3 or more per 1000 molecular weight of the triorganosiloxane (B). It is more preferred that the number of the branched polyorganosiloxanes (B) is 12 or less per 1000 molecular weight. or 9 or less per 1,000 molecular weight of the branched polyorganosiloxane (B). By making the total content of the soluble functional group and the compatible group equal to or more than the lower limit, compatibility with the resin can be improved. By reacting with the resin, the branched polyol is attached to the surface, which improves the properties and makes it easier to obtain a transparent composition. The fixation of siloxane (B) improves the durability of the resin surface against scratches. In addition, the total content of the reactive functional group and the compatible group is set to the above upper limit or less. This makes it easier for the branched polyorganosiloxane (B) to segregate near the surface, improving scratch resistance. can be made even higher.
[0032] The reactive functional group is not particularly limited, but may be an alkenyl group, an ester group, a methacryloyl group, Acryloyl groups, cyclic ether groups, and alcoholic hydroxyl groups are highly reactive. An alcoholic hydroxyl group is preferred, and an alcoholic hydroxyl group is more preferred.
[0033] The alkenyl group may have a branched structure or a cyclic structure. An alkenyl group is more preferably an alkenyl group having 2 to 6 carbon atoms, and even more preferably is a vinyl group, a propenyl group, an isopropenyl group, or a butenyl group, and particularly preferably a vinyl group. It is a aryl group. The small number of carbon atoms results in a small non-polar portion, which makes it easier to bond to the polycarbonate resin (A). The alkenyl group is preferably an alkenyl group having an internal olefin structure. and those having a terminal olefin structure. Those having a terminal olefin structure are preferred.
[0034] The ester group is a group represented by formula (3) or formula (4). [ka] [ka] (In formula (3), g=0 or 1, and in formula (4), h=0 or 1.) R in formula (3) and formula (4) 8 is a monovalent group, and may include a branched or cyclic structure. From the viewpoint of compatibility and reactivity with polycarbonate resin (A), R 8 As is preferably an organic group having 1 to 20 carbon atoms, and more preferably an organic group having 1 to 6 carbon atoms. The small number of carbon atoms results in little steric hindrance, and the reaction of the ester group is less inhibited. In addition, the smaller the number of carbon atoms, the smaller the non-polar portion, and the smaller the polycarbonate. This is preferable because it increases the compatibility with the resin (A).
[0035] On the other hand, when prioritizing improvement of scratch resistance, a larger number of carbon atoms may be advantageous. A hydrocarbon group having 6 to 30 carbon atoms is preferred, and a hydrocarbon group having 10 to 30 carbon atoms is more preferred. When the carbon number is large, the hydrocarbon group approaches crystallization near the surface of the polycarbonate resin (A). This is preferable because it forms a thin structure and improves the scratch resistance of the surface. R in formula (3) and formula (4) 9 is a divalent group, and is an ester group and a polyorganosiloxane R is a group that bonds 9 is not particularly limited as long as it is a divalent group, and may be a branched or cyclic structure. It may contain atoms other than carbon and hydrogen atoms, but may contain 1 to 2 carbon atoms. It is preferably an organic group having 20 carbon atoms, and more preferably an organic group having 1 to 10 carbon atoms. The smaller number of carbon atoms results in a smaller non-polar portion, making it easier to mix with polycarbonate resin (A). This is preferable because it increases the compatibility of the
[0036] There are no particular limitations on the methacryloyl group and acryloyl group as long as they have these structures. However, from the viewpoint of high reactivity and compatibility, methacryloyloxy and acryloyloxy groups are It is preferably an aryloxy group. Also, it is bonded to the polyorganosiloxane via a divalent group. It is preferable that the divalent functional group is also described in formula (3) and formula (4). R 9 However, methacryloyl groups, acryloyl groups, methacryloyl groups, R bonded to oxy group or acryloyloxy group 9 is preferably an organic group having 1 to 20 carbon atoms. It is more preferable that the organic group has 1 to 10 carbon atoms. This is preferred because it reduces the size of the non-polar portion and improves compatibility with the polycarbonate resin (A). .
[0037] The cyclic ether group is not particularly limited as long as it is a group having a cyclic ether structure, but is preferably It is preferably a group represented by formula (5) or formula (6). [ka] [ka] (In formula (5), i = 0 or 1, and in formula (6), j = 0 or 1, 0 ≦ k ≦ 8, 0 ≦ m ≦ 8.) R in formula (5) and formula (6) 10 is a divalent group, and is a cyclic ether group and a polyorganosilyl group. R is the group that bonds the oxysilane. 10 is not particularly limited as long as it is a divalent group, and may be a branched structure or It may contain a cyclic structure and may contain atoms other than carbon and hydrogen atoms, but It is preferably an organic group having 1 to 20 carbon atoms, and more preferably an organic group having 1 to 10 carbon atoms. It is preferable that the number of carbon atoms is small, and the non-polar portion is small, so that the polycarbonate resin This is preferred because it increases the compatibility with (A).
[0038] More preferred are groups represented by formula (7), formula (8) and formula (9). [ka] [ka] [ka] The groups represented by formula (7), formula (8), and formula (9) all exhibit high reactivity and high polarity. Since the polycarbonate resin (A) is highly compatible with the polycarbonate resin (A), the above-mentioned formula (10) is preferable. ), a group having an ester group in addition to a cyclic ether group, such as a group represented by formula (11) preferable. [ka] [ka] The groups represented by formula (10) and formula (11) include, in addition to a cyclic ether group, a highly polar ester group. Since it also has a group, high compatibility with the polycarbonate resin (A) can be expected.
[0039] The alcoholic hydroxyl group is not particularly limited as long as it has a structure having a hydroxyl group bonded to a carbon atom. Although one organic group may have one or more hydroxyl groups, the organic group represented by the formula (12) The group represented by the formula (I) is preferred. [ka] R in Equation (12) 11 is a divalent organic group, and is composed of an alcoholic hydroxyl group and a branched polyorgano R is a group that bonds siloxane.11 is not particularly limited as long as it is a divalent group, or a cyclic structure, and may contain atoms other than carbon and hydrogen atoms, The organic group preferably has 1 to 20 carbon atoms, and more preferably has 1 to 10 carbon atoms. The smaller the number of carbon atoms, the smaller the non-polar portion, and the smaller the polycarbonate resin. This is preferable because it increases the compatibility with the fat (A). 11 Oxygen, sulfur, and nitrogen atoms When the aryl group contains an atom, the polarity becomes high and the compatibility with the polycarbonate resin (A) becomes high. For example, a group represented by formula (13) is more preferred, and a group represented by formula (14) is more preferred. More preferred is a group represented by the formula: [ka] (In formula (13), R 12 is a divalent organic group, and R 13 , R 14 , R 15 , R 16 is the same or different, a hydrogen atom or a monovalent organic group having 1 to 10 carbon atoms; 1≦n≦100.) [ka] The groups represented by the formulas (13) and (14) have high polarity and are easily reacted with the polycarbonate resin (A). In particular, the group represented by formula (14) has a small steric hindrance. Therefore, it is preferable because it has excellent reactivity.
[0040] The compatible group is an interionic phase with respect to the whole or part of the constituent elements of the polycarbonate resin (A). Polycarbonate resin (A) and There are no particular limitations on the type of group as long as it is a group that improves the compatibility of the branched polyorganosiloxane (B). The group may be reactive in addition to being soluble. Considering that the polycarbonate resin (A) is a polar resin, the polar groups, i.e. A group having one or more of an aromatic group, an oxygen atom, a sulfur atom, and a nitrogen atom. More specifically, the group having an aromatic group is preferably a phenyl group, a naphthyl group, or the like. anthracenyl, biphenyl; and alcoholic hydroxyl groups, as groups having oxygen atoms. groups, polyalkylene glycol groups, cyclic ether groups, ester groups; groups having a sulfur atom and As groups having a nitrogen atom, mercapto groups, thiirane groups, and polyethylene sulfide groups are used. Amino group, monoalkylamino group, dialkylamino group, aziridine group, azetidine group , pyrrolidine group, piperidine group are preferred, and phenyl group, ester group are preferred. This is more preferred in terms of high compatibility with the resin (A). In addition, the linear alkyl group has low polarity and improves compatibility with the polycarbonate resin (A). However, the polycyclic aliphatic hydrocarbon group close to the isosorbide skeleton is not compatible with isosorbide. Since it has an intermolecular interaction with the rubido skeleton, it is suitable as a compatible group. The pentanyl group is preferred.
[0041] R in the above formula (2) 1 From R 6 When is not a reactive functional group or a compatible group, these The structure is not particularly limited, but each independently represents a hydrogen atom or a monovalent hydrocarbon having 1 to 20 carbon atoms. Specifically, it is a hydrogen atom, a linear alkyl group having 1 to 20 carbon atoms, and alkyl groups having a cyclic structure having 1 to 20 carbon atoms. Of these, hydrogen atom, methyl group, ethyl group, propyl group, isopropyl group, butyl group Preferred are alkyl groups such as butyl, s-butyl, t-butyl, octyl, and cyclohexyl. A hydrogen atom or a methyl group is more preferred.
[0042] In the branched polyorganosiloxane (B), a represents the proportion of M units in formula (2). is 0≦a<1, but is preferably 0.1 or more, and more preferably 0.15 or more. In addition, a is less than 1, preferably 0.8 or less, and more preferably 0.7 or less. By setting the M unit to the above lower limit or more, an undesired increase in molecular weight can be suppressed, As a result, the increase in viscosity can be suppressed, which is preferable from the viewpoint of ease of handling. By keeping the molecular weight below the limit, it becomes easier to keep the molecular weight within an appropriate range that is not too small, and low boiling point components can be obtained. This is preferable in that an increase in the amount of
[0043] The type of siloxy unit of the M unit in the branched polyorganosiloxane (B) is not particularly limited. However, it is preferable that the amount of trimethylsiloxy groups in all M units is 50 mol % or less. , more preferably 25 mol % or less, and even more preferably 5 mol % or less; It is particularly preferable that the trimethylsiloxy group is 0 mol %. Since this may reduce the compatibility with the polycarbonate resin (A) to be used, By making the trimethylsiloxy group of the above-mentioned upper limit value or less, it is possible to obtain a poly(isosorbide skeleton) having an isosorbide skeleton. Transparent resin composition containing carbonate resin (A) and branched polyorganosiloxane (B) This is preferable in that it is possible to maintain high stability.
[0044] In the branched polyorganosiloxane (B), b represents the proportion of D units in formula (2). is 0≦b<1, but is preferably 0.8 or less, and more preferably 0.5 or less. By setting the D unit to the above upper limit or less, the molecule becomes linear. As the shape of the molecule approaches a sphere, the branched polyorganosiloxane molecules radiate outward. The reactive functional group and / or the compatible group are arranged in a structure. Since the groups are easily brought into contact with the polycarbonate resin (A), This is preferred because it makes it easier to coordinate with the polar element in the compound, thereby improving compatibility.
[0045] In addition, in formula (2), c, which indicates the proportion of T units, and d, which indicates the proportion of Q units, are 0 <c+d However, it is preferable that 0.15≦c+d, and more preferable that 0.4≦c+d. In addition, c+d≦1, preferably c+d≦0.9, and more preferably c+d≦0 By setting c+d to the above upper limit or less, the branched polyorganosiloxane (B) This is preferable because it is easy to maintain the viscosity of the composition in a manageable range. In addition, by setting c+d to the above lower limit, the molecule approaches a spherical shape from a linear shape. From the branched polyorganosiloxane molecule, reactive functional groups and / or compatible functional groups radiate outward. The reactive functional group and / or the compatible group are polycarbonate resin ( Since it comes into contact with polycarbonate resin (A), it is easy to coordinate with the polar elements in polycarbonate resin (A). This is preferable since it improves compatibility.
[0046] The branched polyorganosiloxane (B) was an MQ resin consisting of M units and Q units. It may be an MT resin consisting of M units and T units, or it may be an MT resin consisting of D units and T units. It may be a DT resin consisting of D units and Q units, or it may be a DQ resin consisting of D units and Q units. , TQ resin consisting of T units and Q units. Alternatively, the MDT resin may be composed of M units, D units and T units. The MDQ resin may be composed of M units, T units and Q units, It may be an MTQ resin, or a DTQ resin consisting of D units, T units and Q units. Alternatively, it may be an MDTQ resin consisting of M units, D units, T units and Q units. Among these, MTQ resin and MQ resin are preferred.
[0047] In formula (2), (O 1 / 2 R 7 The structural unit represented by the formula (B) is a branched polyorganosiloxane. This means the terminal alkoxy groups bonded to the silicon atoms in the branched polyorganosiloxane. The content of alkoxy groups bonded to silicon atoms relative to the total weight of (B) is not particularly limited. is preferably 0.07% by weight or more, more preferably 0.5% by weight or more, and The alkoxy group content is preferably 4% by weight or less, more preferably 2% by weight or less. By doing so, the steric repulsion of the alkoxy group causes the polyorganosiloxane (B) Since the aggregation of molecules is suppressed, it tends to become liquid rather than solid, and shows moderate fluidity. This makes it easier to mix with other resins, etc., and greatly improves the productivity when producing the composition. In addition, by controlling the alkoxy group content to the above upper limit or less, The storage stability of the product is improved, and the alkoxy group is eliminated by heating to produce alcohol. This is preferable in terms of the safety and health of workers, as it suppresses the phenomenon of the metal oxide becoming hot.
[0048] R 7 As the alkyl group, a methoxy group, an ethoxy group, and an isopropoxy group are preferable, but the alkyl group is not limited thereto. It is not something that can be done.
[0049] The number average molecular weight (Mn) of the branched polyorganosiloxane (B) is not particularly limited, but is preferably 5 It is preferable that the number of the sieving agents is 1000 or more, and more preferable that the number of the sieving agents is 800 or more. It is preferable that Mn is 00 or less, and more preferable that Mn is 10000 or less. By setting the Mn content to the lower limit or more, it is preferable in that the amount of volatile components is small. This is preferable in that the viscosity is low and the handling properties are improved.
[0050] The weight average molecular weight (Mw) of the branched polyorganosiloxane (B) is not particularly limited, but It is preferably 700 or more, and more preferably 1000 or more. It is preferable that Mw is 0,000 or less, and more preferably 15,000 or less. By setting the Mw to the above lower limit or more, it is preferable in that the amount of volatile components is small. The above-mentioned range is preferable in that the viscosity is low and the handling property is improved.
[0051] The above-mentioned Mn and Mw were determined by gel permeation chromatography (GPC ) and calculated using a calibration curve with polystyrene standard samples. Refers to the Ren equivalent value.
[0052] The amount of the low boiling point component contained in the branched polyorganosiloxane (B) is not particularly limited, but If the amount of low boiling point components is small, the flash point becomes high, making it difficult to maintain safety during transportation and storage. In addition, volatile components are vaporized during mixing with polycarbonate resin (A) and molding, The branched polyorganosiloxane of the present invention is preferable because it is unlikely to cause problems such as contamination of the equipment. The amount of the low boiling point component contained in the alkane (B) is, for example, It can be expressed as the weight loss rate when heated at 110°C for 2 hours, and this weight loss rate is 10 % by weight or less, more preferably 8% by weight or less, and still more preferably 5% by weight or less. It is more preferable that the temperature is lower than the above range.
[0053] The branched polyorganosiloxane (B) may have a cage structure in addition to the branched structure. The branched polyorganosiloxane (B) may not have a cage structure. In this case, the branched polyorganosiloxane (B) becomes a very rigid molecule. This is preferred in that the elastic modulus of the composition obtained by mixing with the carbonate resin (A) is improved. In addition, when the branched polyorganosiloxane (B) does not have a cage structure, This is preferable from the viewpoint of ease of handling since the viscosity is reduced as compared with the case where the resin is used.
[0054] Regarding whether the branched polyorganosiloxane (B) has a cage structure, This can be confirmed using infrared absorption spectroscopy. Wavenumber: 1000-1200 cm -1 In infrared absorption spectroscopy in the region of 1070 to 1080, the cage structure is 1150cm -1 The Si-O stretching vibration absorption peak is in the region. If not, the wave number is 1030 to 1060 cm -1 The maximum absorption of Si-O stretching vibration occurs in the region The wave number is 1070 to 1150 cm -1 In the region, Si- There are characteristic absorption bands due to organic molecules other than O. For example, CO-derived bands of hydroxyl groups Next, COC-derived esters, COC-derived acid anhydrides, and COC-derived ethers. , CN origin of amines, CS origin of sulfonic acids and sulfoxides, CF origin of fluorine compounds Derived from phosphorus compounds P=O or PO, inorganic salt SO4 2- or ClO4 - Caused by These are known to have structures with high absorption intensities, and the assignment of these to the Si-O stretching vibrations has been You must be careful not to confuse them.
[0055] The method for producing the branched polyorganosiloxane (B) of the present invention comprises the steps of: There are no particular limitations as long as a polyorganosiloxane having the structure can be obtained. For example, Siloxane compounds, disilazane compounds and their hydrolysates, alkoxysilane compounds or its hydrolyzate or partial hydrolysis condensate, A method for condensing silane compounds, their hydrolysates, and partial hydrolysis condensates, Any of the methods for producing the compound, such as ring-opening polymerization, anionic polymerization, and chain polymerization, can be used. A plurality of manufacturing methods may be used in combination. In addition, there is no particular limitation on the method for introducing the reactive functional group or the compatible group. Alkoxysilane compounds, disiloxane compounds, disilazanes, and / or compounds having compatible groups Condensation of one or more of these compounds, their hydrolyzates, or partial hydrolysis condensates simultaneously The method is to convert a different type of group introduced into polyorganosiloxane into a reactive functional group by a chemical method. and / or a method of converting the carboxylic acid group into a compatible group, or these methods may be used in combination. stomach.
[0056] As a method for converting a different type of group into a reactive functional group and / or a compatible group by a chemical method, A reactive functional group is added to a polyorganosiloxane having a structure in which a hydrogen atom is directly bonded to a silicon atom. and / or a method of reacting a compound having a compatible group with an alkenyl group (hydrosilylation method) ) etc.
[0057] After the reaction, the obtained polyorganosiloxane was subjected to column chromatography. The desired epoxy equivalent and molecular weight can be obtained by using a method such as GPC, solvent extraction, and distillation of unnecessary components. The polyorganosiloxane having the above structure may be fractionated and used. The low boiling point components may be removed by
[0058] The branched polyorganosiloxane (B) may or may not be produced in the presence of a solvent. When a solvent is used, water and organic solvents can be used, but organic solvents are particularly preferred. Tetrahydrofuran, toluene, hexane, heptane, acetone, ethyl acetate, meth More preferred are alcohol, ethanol, isopropanol, chloroform, and dichloromethane. From the viewpoints of solubility, ease of removal, and low environmental hazard, tetrahydrofuran, toluene, and methyl In addition, two or more of these water and organic solvents may be used in combination. The type of solvent may be different depending on the reaction step. Polyorganosiloxane skeleton is formed by hydrolysis and condensation of compounds such as chlorosilane compounds. When the compound is formed, water can be added in an appropriate amount to promote hydrolysis.
[0059] The reaction temperature for producing the branched polyorganosiloxane (B) is not particularly limited, and is usually The reaction temperature is -40 to 200°C, preferably -20 to 150°C, and more preferably 0 to 130°C. At temperatures below this range, the desired polyorganosiloxane skeleton is not formed. Reactions for forming a cross-linked structure and reactions for introducing reactive functional groups and / or compatible groups are difficult to proceed. On the other hand, at temperatures higher than this range, the reactive functional groups and / or compatible groups may be Undesirable reactions such as decomposition of the compound may occur.
[0060] In the preparation of the branched polyorganosiloxane (B), the pressure for carrying out the reaction is not particularly limited. Pressure is not specified, and is usually 0.6 to 1.4 atm, but 0.8 to 1.2 atm may be used. It is preferable to carry out the reaction at a pressure of 0.9 to 1.1 atm. At low pressures, the boiling point of the solvent decreases, making it difficult to raise the reaction temperature to an appropriate level. On the other hand, at pressures higher than this range, the boiling point of the solvent increases, and the reaction Although it has the advantage of accelerating the reaction by increasing the temperature of the reaction system, the reaction is carried out under pressurized conditions. This poses the risk of equipment damage or explosion.
[0061] [Resin composition] The content of branched polyorganosiloxane (B) is 100% by mass of polycarbonate resin (A). The amount of the sintered body is preferably 0.01 parts by mass or more, and from the viewpoint of improving wear resistance, 0.05 parts by mass. The upper limit is preferably 10 parts by mass or less from the viewpoint of transparency and retention of physical properties. It is preferable that the amount is 5 parts by mass or less, and more preferable that the amount is 5 parts by mass or less.
[0062] The present invention relates to a polycarbonate resin (A) having an isosorbide skeleton and a branched polycarbonate resin (B). The resin composition containing the organosiloxane (B) is a branched polyorganosiloxane as defined in the present invention. The polyorganosiloxane (B') may contain a polyorganosiloxane other than the polyorganosiloxane (B). The content of the branched polyorganosiloxane (B') is not particularly limited, but ) 100 parts by mass, it is preferably 500 parts by mass or less, and more preferably 100 parts by mass or less. It is more preferable that the content be 50 parts by mass or less, and further more preferable that the content be 50 parts by mass or less. By setting the content of polyorganosiloxane (B') to the above upper limit value or less, The present invention provides a resin composition comprising a carboxylate resin (A) and a branched polyorganosiloxane (B) and capable of improving transparency. This is preferable in that the temperature can be kept low.
[0063] [Additives] The polycarbonate resin composition may further contain, within the range not impairing the above-mentioned desired effects. Various additives can be added. Additives include catalyst deactivators, antioxidants, ultraviolet ray inhibitors, etc. X-ray absorbers, light stabilizers, release agents, colorants, neutralizing agents, antistatic agents, lubricants, plasticizers, These include fuels and fillers.
[0064] (Catalyst deactivator) The catalyst deactivator has the property of deactivating the polymerization catalyst of the polycarbonate resin (A). It can improve the color tone of recarbonate resin and improve its thermal stability. As the solvent deactivator, for example, an acidic compound can be used. Examples of the compounds include compounds having a carboxylic acid group, a phosphoric acid group, or a sulfonic acid group, and their esters. The body, etc. can be used.
[0065] (Antioxidants) As the antioxidant, any antioxidant commonly used in resins can be used. Oxidation stability From the viewpoints of thermal stability, good jet blackness when colored, etc., phosphite-based antioxidants, The antioxidant is preferably an ethylenic antioxidant or a phenolic antioxidant. A mixture of these compounds may be used, or two or more compounds may be used in combination.
[0066] (Ultraviolet absorber (C)) The polycarbonate resin composition may contain an ultraviolet absorber within the range not impairing the object of the present invention. Examples of the ultraviolet absorbing agent include 2-(2'-hydroxy-5'- t-Octylphenyl)benzotriazole, 2-(3-t-butyl-5-methyl-2- 2-(2'-hydroxy-5- 2-[2-hydroxy-3,5-bis(α,α-methylphenyl)benzotriazole dimethylbenzyl)phenyl]-2H-benzotriazole, 2-(2H-benzotriazole 2,2-(1,1,3,3-tetramethylbutyl)phenol '-p-phenylenebis(1,3-benzoxazin-4-one). The content of the absorbent is preferably 0.01 to 2 parts by mass per 100 parts by mass of the polycarbonate resin. The content is preferably 0.05 to 1 part by mass, and more preferably 0.05 to 1 part by mass.
[0067] (Light stabilizer (D)) The polycarbonate resin composition may contain a light stabilizer within a range that does not impair the object of the present invention. As the light stabilizer, for example, a compound derived from an amine compound can be used. Preferably, the compound has a melting point of 85° C. or higher and a secondary amine structure. Compounds with a secondary amine structure are more basic than primary amines. The higher the basicity of the light stabilizer, the higher the stability of the polycarbonate against light. , degradation due to hydrolysis is suppressed.
[0068] From the viewpoint of reducing the rate of change of molded products before and after light resistance testing, The amine structure is preferably one in which the nitrogen is part of a cyclic structure, and has a piperidine structure. The piperidine structure defined herein is preferably a saturated 6-membered cyclic amine structure. As long as the piperidine structure is substituted with a substituent, it can have any structure. The piperidine structure may have a substituent having 4 or more carbon atoms. The following alkyl groups are exemplified, and a methyl group is particularly preferred.
[0069] Compounds having a melting point of 85°C or higher and a secondary amine structure include those having a secondary amine structure. It is preferable that the secondary amine structure of the piperidine structure is a plurality of the secondary amine structures. More preferably, a compound having a plurality of piperidine structures linked by an ester structure is used. Compounds that have been shown to be effective are preferred.
[0070] From the viewpoint of improving bleed-out resistance, polycarbonate resin (A) and ammonia The absolute value of the difference in solubility parameter (i.e., SP value) between the carboxylic acid compound and the carboxylic acid compound is preferably 0.0 to 15.0. The SP value is calculated by the Hoy method. From this viewpoint, the absolute value of the difference in the SP values is more preferably 0.0 to 12.0, and even more preferably 0.0 to 8.0. It is particularly preferably 0.0 to 6.0.
[0071] The melting point of the light stabilizer is preferably 85°C or higher. In this case, the average It is possible to improve lubricity and bleed-out resistance. From the viewpoint of the above, the melting point of the light stabilizer is more preferably 90 to 300° C., and further preferably 100 to 250° C. A temperature range of 110 to 200°C is preferable, and a temperature range of 110 to 200°C is particularly preferable.
[0072] In addition, from the viewpoint of improving weather resistance with a small amount, the terminal functional group equivalent of the light stabilizer is 1. The preferred range is 00 to 500 g / eq. This is because a smaller amount is needed to improve weather resistance. Therefore, the terminal functional group equivalent of the photostabilizer is more preferably 100 to 350 g / eq, and more preferably 100 to 30 0 g / eq is even more preferred.
[0073] From the viewpoint of further improving the weather resistance of the molded product, the molecular weight of the light stabilizer is set to 5,000 or less. is preferable, and 3000 or less is more preferable. In order to further suppress contamination and deterioration of the surface appearance, the molecular weight of the light stabilizer is 300 or more. is preferable, and 400 or more is more preferable.
[0074] Such light stabilizers (D) include 2,2,6,6-tetramethyl-4-piperidino tetrakis(2,2,6,6-tetramethyl-4-piperidyl)butane-1,2, 3,4-Tetracarboxylate, bis(1,2,2,6,6-pentamethyl-4-piperidine) Lysyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl butyl malonate, 1,2,3,4-butanetetracarboxylic acid and 2,2,6,6-tetra β,β,β,β-tetramethyl-2,4,8,10- Condensation product with tetraoxaspiro[5,5]undecane-3,9-diethanol, 1,2, 3,4-Butanetetracarboxylic acid and 2,2,6,6-tetramethyl-4-piperidinol and 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetrahydrofuran Mixed esters with traoxaspiro[5.5]undecane, etc. From the viewpoint of high melting point, tetrakis(2,2,6,6-tetramethyl-4-piperidinyl) diethyl)butane-1,2,3,4-tetracarboxylate (SP value 19.2, melting point 130 ℃), 1,2,3,4-butanetetracarboxylic acid and 2,2,6,6-tetramethyl-4- Piperidinol and 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4 ,8,10-tetraoxaspiro[5.5]undecane mixed ester (SP value 1 8.5, melting point 95°C) is preferred. The light stabilizer (D) may be used alone or in combination of two or more. This is also fine.
[0075] The content of the light stabilizer (D) in the polycarbonate resin composition is 1:1 polycarbonate resin. 000 parts by mass, 0.001 to 5 parts by mass is preferable, and 0.005 to 3 parts by mass is more preferable. The content of the light stabilizer is preferably 0.01 to 1 part by mass, and more preferably 0.01 to 1 part by mass. In addition, when a coloring agent is added, for example, the coloring agent can be added to the liquid to give a sense of depth and clarity. Furthermore, the effect of light resistance is sufficiently obtained, and it is possible to obtain a jet black color with a clear finish, for example, in the interior of a car. A molded article suitable for exterior applications can be obtained.
[0076] As the light stabilizer (D), as described above, for example, an aminated compound having a secondary amine structure can be used. However, an amine compound different from these preferred forms may be used in combination. The amine compound that can be used in combination is preferably an amine compound having a tertiary amine structure. In this case, the effect of photostability can be exerted for a longer period of time. From this viewpoint, the light stabilizer is preferably a secondary amine having a piperidine structure and a piperidine It is more preferable to combine it with a tertiary amine having the structure.
[0077] (Colorant (E)) Examples of colorants include inorganic pigments, organic pigments, and organic dyes and pigments such as organic dyes. The agent may be used alone or in combination of two or more.
[0078] Examples of inorganic pigments include carbon black and oxide pigments. Pigments include titanium oxide, zinc oxide, red iron oxide, chromium oxide, iron black, titanium yellow, zinc- Examples include iron brown, copper-chrome black, and copper-iron black.
[0079] Examples of organic dyes and pigments include phthalocyanine dyes and pigments, condensed polycyclic dyes and pigments, and dyes and pigments. Condensed polycyclic dye pigments include azo, thioindigo, perinone, and perylene. , quinacridone, dioxazine, isoindolinone, quinophthalone, etc. Pigments include anthraquinones, perinones, perylenes, methines, quinolines, and complexes. There are monocyclic and methyl types.
[0080] The coloring agent is preferably an inorganic pigment. In this case, when the molded product is used outdoors, However, image clarity can be maintained for a long period of time.
[0081] The content of the colorant in the polycarbonate resin composition is 10% by weight of the polycarbonate resin (A). With respect to 0 parts by mass, 0.05 to 5 parts by mass is preferable, and 0.05 to 3 parts by mass is more preferable. By adjusting the content of the colorant within the above range, It is possible to obtain a dyed molded product with high image clarity and to prevent an increase in the surface roughness of the molded product. can be done.
[0082] When the polycarbonate resin composition is toned to a jet black tone, the lightness L * is 0.1 to 10 It is preferable that the gloss is 85%, and more preferably 0.1 to 6. More than this is preferable, and 88% or more is even more preferable.
[0083] (Filler) The polycarbonate resin composition may contain inorganic fillers, organic fillers, etc., within the range in which the design properties can be maintained. The filler may contain inorganic fillers such as glass fiber, glass microparticles, etc. Glass fiber, glass flakes, glass beads, silica, alumina, titanium oxide, sulfuric acid Calcium powder, gypsum, gypsum whiskers, barium sulfate, talc, mica, wollastonite Calcium silicate such as tungsten, carbon black, graphite, iron powder, copper powder, molybdenum disulfide Silicon carbide, silicon carbide fiber, silicon nitride, silicon nitride fiber, brass fiber, stainless steel Examples of organic fillers include fibers, potassium titanate fibers, and whiskers thereof. Powdered organic fillers such as wood flour, bamboo flour, palm starch, cork flour, pulp flour, etc.; crosslinked polyester Balloon-shaped or spherical organic fillers such as polystyrene, styrene-acrylic copolymers, and urea resins ; fibrous organic fillers such as carbon fibers, synthetic fibers, and natural fibers.
[0084] (lubricant) The polycarbonate resin composition may contain a lubricant within the range not impairing the object of the present invention. Lubricants are also called flow improvers. Examples of lubricants include fatty acid amides, para Oils made of hydrocarbon compounds such as fin oil, silicone oil, carboxylic acid ester Examples of the wax include ester compounds such as ethylhexyl ether and fluorine-based wax. From the viewpoint of maintaining physical properties, fatty acid amides are preferred.
[0085] [Method for producing polycarbonate resin composition] The polycarbonate resin composition is prepared by mixing the above components in a predetermined ratio at the same time or at random. In order, the following equipment is used: tumbler, V-type blender, Nauta mixer, Banbury mixer, kneader, The composition can be produced by mixing the components in a mixer such as a roll or an extruder. By mixing the carbonate resin (A) and the branched polyorganosiloxane (B), A polycarbonate resin composition can be produced. In addition, ultraviolet absorbents, light stabilizers, etc., which are added in advance, can be used in combination.
[0086] [Molded products] The molded article can be obtained by molding the polycarbonate resin composition. For example, injection molding, injection compression molding, injection press molding, etc. The runners used in molding are preferably cold runners, hot runners, It is also possible to use either the insert molding or in-mold molding method. Coating molding, two-color molding, sandwich molding, etc. are also possible. From the viewpoint of increasing the heat dissipation, it is also possible to use heat-insulating mold molding and rapid heating and cooling mold molding. .
[0087] (Application) For example, even without painting, the molded product has excellent abrasion resistance and can be wiped clean with a cloth or other cleaning materials. There are few scratches that occur when wiping with tissue, etc., and it is effective when wiping off muddy water containing environmental dust. Therefore, the process for painting and the cost can be reduced. Because of these effects, molded products can be used in a variety of parts. Moreover, the molded product has excellent smoothness and can be made more transparent by selecting additional materials. It is also possible to add light stabilizers, purple pigments, etc., which can improve the sharpness, etc. By adding ultraviolet ray inhibitors, it has excellent transparency and other effects even in environments exposed to light. It is believed that this will enable the effect to be maintained for a long period of time. However, the molded product may be not only transparent but also colored as mentioned above. This includes those with colored agents. Because of the above effects, the molded product can be a high-quality part with a luxurious and solid feel. There are no particular limitations on the applications of the molded products, but they are widely used in housing materials, film parts, etc. Materials, building materials, interior and exterior products, interior and exterior parts for automobiles and other vehicles It is suitable for.
[0088] Examples of automotive exterior parts to which molded articles are applied include fenders, bumpers, and Face covers, door panels, side garnishes, pillars, radiator grilles, side protectors ctors, side moldings, rear protectors, rear moldings, various spoilers, bonnets, Roof panels, trunk lids, detachable tops, window reflectors, mirrors Examples of interior parts for automobiles include: Instrument panels, center console panels, meter parts, various switches, Car navigation parts and car audio-visual parts. The molded product can be used for mobile computer parts, etc. However, the present invention is not limited to these applications.
[0089] <Reasons why the present invention is effective> The reason why the present invention is effective is not yet clear, but is presumed to be as follows. By using branched polyorganosiloxane, wear resistance is improved and the use of molded products is improved. In addition, the reactive functional group and / or the compatible group can prevent scratches and abrasion that may occur sometimes. By using the branched polyorganosiloxane introduced, the reactive functional group and the polycarbonate Reaction with the polycarbonate resin, coordination of the compatible group portion to the polar element of the polycarbonate resin, or molecular The interactions between them cause dispersion at the molecular level, allowing transparency to be maintained. In addition, due to the low surface free energy of the polysiloxane portion, branched polyorgano Siloxane segregates to the surface of the molded product, preventing domain or film formation due to segregation. This buffers the stress that acts on the polycarbonate resin during wear, and causes stress relaxation. This reduces wear and tear, and allows the glass to withstand environmental dust while still maintaining the high transparency mentioned above. It is believed that this will reduce wear and tear caused by wiping off muddy water. As a result, the polycarbonate resin composition enables the production of high-quality molded products with improved aesthetics. to.
[0090] In contrast, polyorganosiloxanes that do not have reactive functional groups and / or compatible groups However, the compatibility at the interface between polyorganosiloxane and polycarbonate resin is poor, resulting in incompatibility. It is believed that this will result in the formation of insoluble interfaces and a decrease in the transparency of the molded product as a whole. When a polyorganosiloxane with a low molecular weight is used, the viscosity of the polymer is reduced to relieve stress. It is considered that the dissipation of energy is insufficient, making it difficult to improve wear resistance. On the other hand, if the molecular weight is too high, the kneading energy will be insufficient during the kneading process. It becomes difficult to disperse the polyorganosiloxane sufficiently in the resin, and the dispersion size of the polyorganosiloxane becomes large, It is believed that the desired abrasion resistance and transparency cannot be obtained due to the occurrence of scattering unevenness. EXAMPLES
[0091] The present invention will be described in more detail with reference to the following examples, but the present invention does not exceed the gist of the present invention. However, the present invention is not limited to the following examples. In the following description, "parts" and "%" refer to "parts by mass" and "% by mass", respectively. show.
[0092] [Evaluation method] The physical properties and characteristics of the polycarbonate resin and polycarbonate resin composition are described below. The evaluation of the properties was carried out by the following method.
[0093] (1) Test piece preparation method The polycarbonate resin composition pellets were dried at 100°C for 8 hours under a nitrogen atmosphere. Next, the dried pellets were fed into an injection molding machine (Toshiba Machine Co., Ltd. EC-75SX). At a resin temperature of 240°C and a mold temperature of 60°C, an injection molded plate (width 100 mm x length 100 mm x width 100 mm) was A thickness of 2 mm was molded. This injection molded plate was used as the test piece.
[0094] (2) Coefficient of kinetic friction The test piece obtained in (1) above was indented with a ball indenter made by Shinto Scientific (material: SUS, size: φ3mm) using a surface texture measuring instrument (SHINTO Scientific, model: HEIDON-14D). The dynamic friction coefficient was calculated from the load when the load was 200 gf and the moving speed was 100 mm / min. The average value of the load from 4 to 10 seconds after the start of movement was used as the few μk.
[0095] (3) Tissue abrasion test The tissue scratch test was performed using a surface property measuring instrument (manufactured by Shinto Scientific Co., Ltd., model: Tribogear TY First, tissue (Nippon Paper Crecia Flower Box) was used. The paper was folded three times and attached to a φ28mm steel wool holder made by Shinto Scientific. Next, a steel wool holder was placed on the surface of the test piece obtained in (1) above, and the The reciprocating motion was performed with a load of 9.8N, a stroke of 50mm, and a speed of 3000mm / min. After that, the appearance of the scratches was evaluated. Molded products with less than 20 scratches were rated as "O", and molded products with 20 or more scratches were rated as "X".
[0096] (4) Muddy water abrasion test The muddy water abrasion test was performed using a surface property measuring instrument (manufactured by Shinto Scientific Co., Ltd., model: Tribogear TYPE- 14D). The muddy water was made of sodium carboxymethylcellulose manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. Prepare a gel by mixing water in a weight ratio of 1:50, and compare this gel with JIS Z8901 (Type 2). The mixture was mixed in a weight ratio of 5:1 to prepare a liquid. A 20mm square 5mm thick urethane sponge (manufactured by Kosha Co., Ltd.) is placed on a φ28mm Shintosha The specimen was attached to a laboratory steel wool holder and the surface of the specimen obtained in (1) above was subjected to a Using a dropper, drop 0.2g of muddy water, then place a steel wool holder on top of it. The load was 100gf, the stroke was 50mm, and the speed was 6000mm. The test was performed under the conditions of / min. After that, in accordance with JIS Z8722, Konica Minolta Japan Co., Ltd. manufactured CM-5 Using a D65 / 10 light source reflection method, the color of the scratched surface is measured. * ,a * ,b* Measure the wear Color difference ΔE before and after the test * The smaller this value, the better the scratch resistance. .
[0097] (5) Total light transmittance Using the test piece obtained in (1) above, NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd., and a D65 light source, The test was performed in accordance with JIS K7105.
[0098] (6) Measurement of reactive functional groups / compatible groups Weigh out 50 mg of each branched polyorganosiloxane and add 15 mg of toluene as an internal standard. Approximately 1 g of deuterated chloroform was added and dissolved, and the 1 H-NMR( Relaxation Delay was measured for 20 seconds using the JEOL AL-400. The ratio of the signal intensity of each component to the signal intensity of the internal standard toluene and the weight ratio were calculated. The amount indicates the reactive functional group content per gram (mmol / g), i.e., the molecular weight of 1000 The number of reactive functional groups per unit was calculated.
[0099] (7) 29 Si-NMR measurement Equipment: JNM-ECS400 manufactured by JEOL Ltd., TUNABLE(10), Si-free -AT10 probe Measurement conditions: Relaxation Delay / 15 seconds, Scan count / 1024 times, Measurement mode / Non-gated decoupled pulse method (NNE), Spin / None, Measurement temperature / 2 5℃ Sample preparation: Tris(2,4-pentanedionato)c in deuterated chloroform Add chromium III to make it 0.5%. 29 Solvent for Si-NMR measurement was obtained. Weigh out 1.5 g of the polyorganosiloxane to be measured and 29 Si-NMR measurement solution The mixture was dissolved in 2.5 ml of solvent and placed in a 10 mm diameter Teflon (registered trademark) NMR sample tube. .
[0100] (8) Measurement of molecular weight of branched polyorganosiloxane The number average molecular weight (Mn) and weight average molecular weight (Mw) of each polyorganosiloxane were The gel was measured by gel permeation chromatography (GPC) under the following conditions and the standard The sample was a 10% THF solution, and the concentration was adjusted to 0.45 μm before the measurement. The solution was used after filtering through a filter. Equipment: TOSOH HLC-8220 GPC (Tosoh Corporation) Columns: KF-G, KF-401HQ, KF-402HQ, KF-402.5HQ (Showa Wadenko Co., Ltd.), column temperature 40°C Eluent: tetrahydrofuran, flow rate 0.3 mL / min
[0101] [Polycarbonate resin (A)] Polycarbonate resin having isosorbide skeleton to be blended in polycarbonate resin composition The following PC1 and PC2 were used as fats. PC1: D7340R (manufactured by Mitsubishi Chemical Corporation), refractive index 1.500 PC2: D5380R (manufactured by Mitsubishi Chemical Corporation), refractive index 1.499
[0102] [Branched polyorganosiloxane (B)] In Examples 1 to 5 described later, the branched polyols to be blended in the polycarbonate resin compositions The following silicone oils 1 to 5 were used as the siloxane (B). The raw materials, manufacturing method and characteristics of the product are as follows:
[0103] <Raw materials, etc.> 1,3-Divinyl-1,1,3,3-tetramethyldisiloxane (NuSil Tec (Manufactured by hnology) Hexamethyldisiloxane (NuSil Technology) 1,1,3,3-Tetramethyldisiloxane (Nusil Technology) ) Decyltrimethoxysilane (KBM-3103C, Shin-Etsu Chemical Co., Ltd.) Phenyltrimethoxysilane (KBM-103, manufactured by Shin-Etsu Chemical Co., Ltd.) Hexyltrimethoxysilane (Tokyo Chemical Industry Co., Ltd.) Polytetramethoxysilane (Mitsubishi Chemical Corporation MS-51) Ethylene glycol monovinyl ether (Tokyo Chemical Industry Co., Ltd.) Stearyl methacrylate (Tokyo Chemical Industry Co., Ltd.) Toluene (Kishida Chemical Co., Ltd.) Methanol (Kishida Chemical Co., Ltd.) Tetrahydrofuran (Kishida Chemical Co., Ltd.) Heptane (Kishida Chemical Co., Ltd.) 1N Hydrochloric Acid (Kishida Chemical Co., Ltd.) 1N potassium hydroxide solution (Kishida Chemical Co., Ltd.) Platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex Platinum solution (Aldrich, platinum concentration 2%) Silica gel (Kanto Chemical Co., Ltd. Silica gel 60N (spherical, neutral) 63-210μ m)
[0104] <Silicone oil 1> As a raw material for branched polyorganosiloxane, 1,3-divinyl-1,1,3,3-tetramethylphenyl 47.3 parts of tetramethyldisiloxane, 150 parts of decyltrimethoxysilane, phenyltrimethoxysilane 25.2 parts of tetramethoxysilane, 7.34 parts of polytetramethoxysilane, 1 part of toluene as a solvent 15 parts, 115 parts of methanol, 46.2 parts of 1N hydrochloric acid and 46.2 parts of methanol as a catalyst The mixture was used for hydrolysis and condensation at 30°C for 7 hours. After the addition of 95.1 parts, the reaction was further carried out at 30° C. for 30 minutes. 200 parts of toluene was added, and the salt in the system was removed by washing with desalted water. - Using an evaporator, at 76°C and a reduced pressure of 15 torr, no solvent was observed to be distilled off. The solvent was distilled off until the solution was dissolved in water. The mixture was then cooled to room temperature and then cooled to room temperature. The mixture was heated to obtain silicone oil 1, which is a branched polyorganosiloxane. The yield was 138 parts. The obtained silicone oil 1 was heated to 200° C. under a reduced pressure of 0.15 torr at 110° C. After heating for 2 hours, there was almost no weight loss, less than 5%. Reactive Functional Groups / Compatible Groups: Vinyl group 1.5mmol / g Phenyl group 1.7mmol / g Groups other than reactive functional groups / compatible groups: Methyl group 3.3mmol / g Decyl group 5.4mmol / g Coefficients in Equation (2): a=0.18, b=0, c=0.75, d=0.07 Methoxy group content: 2.2% Mn:3300 Mw:5100 Refractive index: 1.467 Kinematic viscosity: 830mPa / s
[0105] <Silicone oil 2> As a raw material for branched polyorganosiloxane, 1,3-divinyl-1,1,3,3-tetramethylphenyl 52.2 parts of tetramethyldisiloxane, 130 parts of hexyltrimethoxysilane, phenyltrimethoxysilane 27.8 parts methoxysilane, 8.09 parts polytetramethoxysilane, toluene as solvent 109 parts, methanol 109 parts, 1N hydrochloric acid 51.0 parts and methanol 51.0 parts as catalyst The mixture was used to carry out hydrolysis and condensation at 30°C for 7 hours. After adding 105 parts of the above, the reaction was further carried out at 30° C. for 30 minutes. 200 parts of toluene was added, and the salt in the system was removed by washing with desalted water. - Using an evaporator, at 76°C and a reduced pressure of 15 torr, no solvent was observed to be distilled off. The solvent was distilled off until the solution was dissolved in water. The mixture was then cooled to room temperature and then cooled to room temperature. The mixture was heated to obtain Silicone Oil 2, which is a branched polyorganosiloxane. The yield was 119 parts. The obtained silicone oil 2 was heated to 2 at 110° C. under a reduced pressure of 0.15 torr. After heating for 2 hours, there was almost no weight loss, less than 5%. Reactive Functional Groups / Compatible Groups: Vinyl group 2.1mmol / g Phenyl group 1.4mmol / g Groups other than reactive functional groups / compatible groups: Methyl group 4.3mmol / g Hexyl group 1.1mmol / g Coefficients in Equation (2): a=0.22, b=0, c=0.71, d=0.07 Methoxy group content: 2.2% Mn:1900 Mw:3200 Refractive index: 1.463 Viscosity: 650mPa·s
[0106] <Silicone oil 3> As a raw material for branched polyorganosiloxane, 1,3-divinyl-1,1,3,3-tetramethylphenyl 49.7 parts of tetramethyldisiloxane, 35.0 parts of decyltrimethoxysilane, phenyltrimethoxysilane 119 parts of methoxysilane, 7.71 parts of polytetramethoxysilane, 1 part of toluene as a solvent 06 parts, methanol 106 parts, 1N hydrochloric acid 48.6 parts and methanol 48.6 parts as a catalyst The mixture was used for hydrolysis and condensation at 30°C for 7 hours. After the addition of 100 parts, the reaction was further carried out at 30° C. for 30 minutes. 200 parts of toluene was added, and the salt in the system was removed by washing with desalted water. - Using an evaporator, at 76°C and a reduced pressure of 15 torr, no solvent was observed to be distilled off. The solvent was distilled off until the solution was dissolved in water. The mixture was then cooled to room temperature and then cooled to room temperature. The mixture was heated to obtain silicone oil 3, which is a branched polyorganosiloxane. The yield was 123 parts. The obtained silicone oil 3 was heated to 110° C. under a reduced pressure of 0.15 torr for 2 After heating for 2 hours, there was almost no weight loss, less than 5%. Reactive Functional Groups / Compatible Groups: Vinyl group 2.4mmol / g Phenyl group 4.9mmol / g Groups other than reactive functional groups / compatible groups: Methyl group 5.0mmol / g Decyl group 1.1mmol / g Coefficients in Equation (2): a=0.28, b=0, c=0.65, d=0.07 Methoxy content: 1.9% Mn:1300 Mw:1700 Refractive index: 1.511 Kinematic viscosity: 4300mPa / s
[0107] <Silicone oil 4> As a raw material for the precursor of silicone oil 4, 1,1,3,3-tetramethyldisiloxane 1040 parts of silane, 422 parts of polytetramethoxysilane, 94 parts of tetrahydrofuran as a solvent 3 parts, and a mixture of 115 parts of 1N hydrochloric acid and 115 parts of methanol was used as a catalyst. Time hydrolysis and condensation were carried out. 938 parts of heptane was added, and the hydrochloric acid was removed by washing with demineralized water. The mixture was then cooled to 76°C and reduced pressure of 15 torr until no more solvent was visible. The solvent was removed by distillation. The mixture was then heated at 120° C. under a reduced pressure of 0.15 torr for 2 hours. A precursor of silicone oil 4 was obtained. The yield was 707 parts. Next, 161 parts of ethylene glycol monovinyl ether was dissolved in 166 parts of toluene. , platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisilyl with a platinum concentration of 2% 0.17 parts of xane complex xylene solution was added and stirred, and then heated to 85°C. 150 parts of the precursor of silicone oil 4 obtained above was dissolved in 166 parts of toluene. The solution was added dropwise over 1 hour, stirred at 85°C for 3 hours, and then stirred at 120°C for an additional 2 hours. Ta. After cooling the solution to room temperature, 150 parts of silica gel was added and stirred for 30 minutes. The solution obtained by filtering off the filtrate was evaporated in a rotary evaporator at 60°C and a pressure of 15 torr. The solvent was distilled off under reduced pressure at 100° C. until no solvent was visible. The mixture was heated under a reduced pressure of 0.15 torr for 2 hours to obtain a branched polyorganosiloxane, silane. Corn oil 4 was obtained. The yield was 233 parts. The obtained silicone oil 4 was subjected to filtration at a pressure of 0 When heated at 110℃ for 2 hours under a reduced pressure of .15 torr, there was almost no weight loss. It was less than 5%. Reactive Functional Groups / Compatible Groups: 2-(2-hydroxyethoxy)ethyl group 4.9mmol / g Groups other than reactive functional groups / compatible groups: Methyl group 12mmol / g Coefficients in Equation (2): a=0.69, b=0.03, c=0, d=0.28 Methoxy group content: Unable to calculate, but was 1.2% in the precursor stage Mn:1800 Mw:2600 Refractive index: 1.458 Kinematic viscosity: 1300mPa / s
[0108] <Silicone oil 5> As a raw material for the precursor of silicone oil 5, 1,1,3,3-tetramethyldisiloxane 833 parts of hexamethyldisiloxane, 252 parts of polytetramethoxysilane, 422 parts of 965 parts of tetrahydrofuran as a solvent, 115 parts of 1N hydrochloric acid and 11 parts of methanol as a catalyst Using 5 parts of the mixture, hydrolysis and condensation were carried out at 30° C. for 4 hours. 938 parts of heptane was added, and the hydrochloric acid was removed by washing with demineralized water. The mixture was then cooled to 76°C and reduced pressure of 15 torr until no more solvent was visible. The solvent was removed by distillation. The mixture was then heated at 120° C. under a reduced pressure of 0.15 torr for 2 hours. A precursor of silicone oil 5 was obtained. The yield was 744 parts. 23.0 parts of the obtained precursor of silicone 5 was dissolved in 32.3 parts of toluene, and then platinum Platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 2% concentration 0.05 parts of the complex xylene solution was added and stirred. After heating to 80°C, methacrylic acid was added. A solution of 7.43 parts of tearyl alcohol dissolved in 7.43 parts of toluene was added dropwise over 1 hour, and then The mixture was stirred at 80° C. for 1 hour. Next, 16.7 parts of styrene was added dropwise at 80°C over 30 minutes, and platinum ( 0)-1,3-Divinyl-1,1,3,3-tetramethyldisiloxane complex xylene solution After adding 0.05 parts, the mixture was stirred at 80°C for 4 hours. After cooling the solution to room temperature, 47.1 parts of silica gel was added and stirred for 30 minutes. The gel was filtered off, and the resulting solution was evaporated in a rotary evaporator at 60°C and a pressure of 15 to The solvent was distilled off under reduced pressure of 1000 rr until no solvent was visible. The mixture was heated at a reduced pressure of 0.15 torr for 2 hours to obtain a branched polyorganosiloxane, silane. Silicone Oil 5 was obtained. The yield was 41.8 parts. The obtained silicone oil 5 was pressurized. When heated at 110°C for 2 hours under a reduced pressure of 0.15 torr, there was almost no weight loss. The rate was less than 5%. Reactive Functional Groups / Compatible Groups: Stearyl ester group: 0.48mmol / g Phenyl group: 3.4mmol / g Groups other than reactive functional groups / compatible groups: Methyl group: 12mmol / g Coefficients in Equation (2): a=0.68, b=0.02, c=0, d=0.30 Methoxy group content: 0.44% Mn:1500 Mw:1900 Refractive index: 1.494 Kinematic viscosity: 270mPa / s
[0109] In Comparative Examples 1 and 2 described below, the following silicone oils 6 and 7 were used. Silicone oil 6: BY16-201 (Toray Dow Corning, carbinol powder) End-modified dimethylsiloxane) Refractive index: 1.412 Kinematic viscosity: 45mm 2 / s(25℃)
[0110] Silicone oil 7: KF54-HV (Shin-Etsu Chemical Co., Ltd., diphenyl dimethicone) Refractive index: 1.503 Kinematic viscosity: 4800mPa / s
[0111] [Ultraviolet absorber (C)] The following benzotriazoles are used as the ultraviolet absorbers (C) to be blended in the polycarbonate resin composition. An azole type was used. Benzotriazole-based UV absorber: LA-29 (ADEKA, 2-(2H-benzotriazole) 4-(1,1,3,3-tetramethylbutyl)-2-isotriazolylphenol , melting point 104℃)
[0112] [Light stabilizer (D)] The light stabilizer (D) to be blended in the polycarbonate resin composition is the following hindered amine. A fluorine-based light stabilizer was used. Hindered amine light stabilizer: LA-57 (ADEKA, tetrakis(2,2,6 ,6-Tetramethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate , SP value 19.2, melting point 130℃) For materials with a range of melting points, the average of the minimum and maximum temperatures is used as the melting point. .
[0113] Colorant (E) To create the evaluation plate, Mitsubishi Chemical carbon black MCF#960 was used. Ta.
[0114] [Example 1] PC1 and PC2 were used as polycarbonate resin (A), and branched polyorganosiloxane was Silicone oil 1 was used as the solvent (B) and LA-29 was used as the UV absorber (C). LA-57 was used as the light stabilizer (D) and MCF#960 was used as the colorant (E). Specifically, for the aforementioned evaluation methods (1) to (4), 90 parts of PC1, 10 parts of PC2, 2, 0.3 parts of silicone oil 1, 0.1 parts of LA-29, 0.1 parts of LA-57, 0.1 parts of MCF#960 was preblended. Regarding the aforementioned evaluation methods (1) and (5), PC1 was 90 parts, PC2 was 10 parts, and PC3 was 0.3 parts. Silicone oil 1, 0.1 parts LA-29, and 0.1 parts LA-57 were pre-blended. After that, each blend was mixed in a twin-screw mixer (TEX3, manufactured by Japan Steel Works, Ltd.). The mixture was then put into a 30 mm screw (SST42BW) and kneaded. While adjusting the absolute vacuum pressure to 10~20kPa using a vacuum pump at one point in the mixer, The cylinder temperature was 230°C, the screw speed was 100 rpm, and the discharge rate was 15 kg / hr. The kneaded material is extruded into strands and pelletized using a strand cutter. A resin composition was obtained, which was then formed into a pellet-shaped sample. The pellet sample was dried in a hot air dryer at 100°C for 5 hours and then subjected to the above-mentioned evaluation. The evaluation was carried out according to methods (1) to (5), and the results are shown in Table 1.
[0115] [Examples 2 to 5] A pellet-shaped sample was obtained in the same manner as in Example 1, except that the composition was changed as shown in Table 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Table 1.
[0116] [Comparative Examples 1 to 3] A pellet-shaped sample was obtained in the same manner as in Example 1, except that the composition was changed as shown in Table 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Table 1.
[0117] [Table 1]
[0118] As shown in Table 1, in Comparative Example 3, which did not contain silicone oil, the abrasion resistance was insufficient. The silicone oil 5 used in Example 5 has a phenyl group and an ester group as a compatible group. The silicone oil 7 used in Comparative Example 2 also has a phenyl group as a compatible group. All of them have a high total light transmittance of 90% or more and are highly transparent, but they have poor slipperiness and abrasion resistance. The silicone oil in Example 5 has a higher viscosity than the silicone oil in Example 5. This is because the silicone oil in Example 5 has a branched structure. Caused by. Silicone oil 4 used in Example 4 and silicone oil 6 used in Comparative Example 1 were Each of these has an alcoholic hydroxyl group as a reactive functional group and / or a compatible group, The total light transmittance is higher in Example 4. This is because Silicone Oil 4 has a branched structure. Therefore, the molecule tends to take a nearly spherical shape, with the alcoholic hydroxyl groups facing outward. Therefore, the polycarbonate resin (A) and the alcoholic hydroxyl group are easily brought into contact with each other, and as a result, Reaction with polycarbonate resin (A) or attachment to the polar sites of polycarbonate resin (A) This is presumably because coordination becomes more likely to occur.
[0119] Furthermore, the silicone oils 1 to 3 used in Examples 1 to 3 each have a reactive functional group and / or a compatible functional group. The vinyl and phenyl groups are functional groups, but as the content increases, the transparency It can be seen that the lubricity and abrasion resistance have been improved while maintaining high surface roughness. Thus, the inclusion of a branched polyorganosiloxane having reactive functional groups / compatible groups This allows molded products to maintain high transparency, improve their appearance, and have improved abrasion resistance. You know you can get it.
Claims
1. The present invention includes the following (A) and (B): The (B) is a polyorganosiloxane having an M unit (R 1 R 2 R 3 SiO 1/2 ) content is 10 mol % or more, and T units (R 6 SiO 3/2 a resin composition comprising a polyorganosiloxane having a content of 80 mol % or less; A polycarbonate resin (A) having an isosorbide skeleton, A branched polyorganosiloxane (B) having at least one group selected from the group consisting of an alkenyl group, an ester group, a methacryloyl group, an acryloyl group, a cyclic ether group, and an alcoholic hydroxyl group as a reactive functional group and / or a compatible group.
2. 2. The resin composition according to claim 1, wherein the branched polyorganosiloxane (B) undergoes a weight loss of 10% by weight or less when heated at 110° C. for 2 hours under a reduced pressure of 0.15 torr.
3. The resin composition according to claim 1 or 2, wherein the branched polyorganosiloxane (B) is liquid at 20° C. under atmospheric pressure.
4. The resin composition according to any one of claims 1 to 3, wherein the reactive functional group of the branched polyorganosiloxane (B) is an alcoholic hydroxyl group.
5. The resin composition according to claim 4 , wherein the alcoholic hydroxyl group includes a structure represented by formula (12). 【Chemistry 1】 (R in formula (12) 11 is a divalent organic group.
6. The number of trimethylsiloxy groups relative to the total number of M units in the branched polyorganosiloxane (B) is 50m. The resin composition according to any one of claims 1 to 5, wherein the content is 1 to 5 mol% or less.
7. The branched polyorganosiloxane (B) is a branched polyorganosiloxane that does not contain a trimethylsiloxy group in its structure. The resin composition according to any one of claims 1 to 6, which is a polyorganosiloxane.
8. A molded article comprising the resin composition described in any one of claims 1 to 7.
Citation Information
Patent Citations
Interior / exterior part of automobile
JP2013209585A
Polycarbonate resin composition and molded part thereof
JP2015199954A
Polycarbonate resin composition and molded article composed of the same
JP2017008140A
Polycarbonate and process for producing the same
WO2004111106A1
Polycarbonate copolymer, production method thereof and use thereof
WO2007063823A1